ФУНКЦІОНАЛЬНА СТРУКТУРА ЕМОЦІЙ ЯК ПСИХІЧНОГО СТАНУ ОСОБИСТОСТІ В СИСТЕМІ ВЗАЄМОДІЇ УЧИТЕЛЯ ТА 5 УЧНЯ (Педагогіка вищої та середньої школи, 2022)
The article is illuminate the problem of the functional structure of emotions at Be system of interaction between the teacher and the pupil. Author singles out and exposes the functions of the person's emotions al the educational process.